2016
DOI: 10.1039/c6ra04532d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave radiation on the activity of catalase. decomposition of hydrogen peroxide under microwave and conventional heating

Abstract: The effect of microwave heating on the activity of a well-known enzyme (catalase) was elucidated by examining the catalase-assisted decomposition of hydrogen peroxide at various heating times (0 to 12 min).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…This clarified that local heating in the enzyme molecule was increased by the effect of the microwaves, thereby causing the deactivation of the enzyme. To confirm this hypothesis, we further clarified that by allowing the enzyme to react at 25 °C (optimal reaction temperature: 37 °C), the reaction promoting effect by the microwaves was maintained 11 . Partial heating field can be suppressed by using PMI because the cooling of the enzyme progresses when the microwaves are turned OFF with respect to microwave heating.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…This clarified that local heating in the enzyme molecule was increased by the effect of the microwaves, thereby causing the deactivation of the enzyme. To confirm this hypothesis, we further clarified that by allowing the enzyme to react at 25 °C (optimal reaction temperature: 37 °C), the reaction promoting effect by the microwaves was maintained 11 . Partial heating field can be suppressed by using PMI because the cooling of the enzyme progresses when the microwaves are turned OFF with respect to microwave heating.…”
Section: Resultsmentioning
confidence: 84%
“…On the other hand, in CMI, the decomposition rate decreased after 3 min. Our previous study (using CMI) showed that using microwaves in catalase reaction can only accelerate the initial degradation rate 11 . This clarified that local heating in the enzyme molecule was increased by the effect of the microwaves, thereby causing the deactivation of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 There are various methods that are able to alter oxidative stress and the activity of catalase, such as heating and microwave radiation. [12][13][14] In a prior study by Sallam and Awad, the effect of the static magnetic field on rat liver has been investigated. 15 They exposed the whole body of rats to magnetic field for one hour each day.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave irradiation as non-conventional energy source plays a leveraged role in chemical transformations (e.g., organic synthesis 1 – 5 , polymer chemistry 6 , 7 , materials science 8 , 9 , nanotechnology 10 and biochemical processes 11 – 14 ). It offers considerable advantages for accelerating chemical reaction, including shortening reaction time, enhancing product yield and purity 15 17 , comparing with conventional heating methods.…”
Section: Introductionmentioning
confidence: 99%